Critical review of movies: developing portuguese language reading skills with deaf students (Research, Society and Development, 2021)
The review is a genre that is very present in our daily lives and suitable for working in Portuguese Language classes, since this genre can provide the reader with information that will help them in the analysis of the work, thus contributing to the choice or not of the purchase/read. In this regard, this work aims to analyze the textual genre critical review of films as a tool for the development of reading skills in Portuguese with deaf students. Its theoretical basis is the studies by Machado; Mascarello and Bakhtin . In this sense, studies like this one are justified by expanding the discussion about the importance of using this genre in Portuguese language classes. In addition, the work is relevant, as it deals with the inclusion of deaf students. Thus, the research contributes towards encouraging pedagogical practices to favor deaf students' critical reading. The results showed that working with a critical review of films can be a good strategy for deaf students to develop reading skills in Portuguese.